Systematic Literature Review (SLR): Implementasi Pendidikan Islam dalam Pembentukan Karakter Anak di Masyarakat: Systematic Literature Review (SLR): The Implementation of Islamic Education in Children's Character Building within Society - Ismatullah, Ade (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2023)
This study examines the implementation of Islamic education in shaping children's character within rural communities, particularly in the context of the Industrial Revolution 4.0 and local wisdom integration. Previous studies predominantly focused on formal institutions, leaving a gap in holistic community-based approaches. Through a qualitative literature review of 12 scholarly articles (2022), this research identifies effective strategies for integrating Islamic values into character education. Findings reveal that collaborativeefforts among families, informal religious institutions (e.g., TPQ), and communities through role modeling, habituation of worship, and consistent moral guidance significantly strengthen children's religious character. The study highlights the critical role of digital adaptation in maintaining relevance amid technological disruptions. Theoretically, it reinforces Bronfenbrenner's ecological model by emphasizing microsystem (family) and mesosystem (community) synergies. Practically, it proposes an integrative